Consultation on a Strategic Environmental Assessment (SEA), partial Business and Regulatory Impact Assessment (BRIA), and Preferred Policy Position on the Scottish Government's long-term policy on onshore unconventional oil and gas in Scotland : analysis of responses /: analysis of responses. (2019) - Griesbach, Dawn; Waterton, Jennifer; Platts, Alison; MacInnes, Mirela
No abstract available